Suppose we have a polynomial satisfying $p+p''' \geq p'+p''$ for all $x$. Then prove that $p(x)\geq 0$ for all $x$.

I've been stuck on this problem for weeks. The best I can do is supposing there exists $x$ so that $p(x) < 0$ (for a contradiction), that we can find a point where $p'=0$, $p''>0$, and $p'''>0$, but I can't use this (nor think of anything new) to show it violates the inequality!

Is there a line of thinking I am missing, or am I only missing something little? Is there a better way to go about proving this?

  • 1
    $\begingroup$ maybe try rearranging into $(p''' - p'') \geq (p' - p)$ to get some symmetry in the picture? $\endgroup$ – Scaramouche Jul 31 '13 at 16:43
  • $\begingroup$ Another thing to note is that $q:=p+p'''-p'-p''$ has the same degree and leading coefficient as $p$; this shows you that $p$ must be of even degree and have positive leading coefficient. $\endgroup$ – Nick Peterson Jul 31 '13 at 17:02
  • 1
    $\begingroup$ Why does this show $p$ is of even degree and has positive leading coefficient? $\endgroup$ – Spine Feast Aug 2 '13 at 21:05

The statement can be slightly stronger:

Claim: If a real polynomial $p$ satisfies that $p+p'''\ge p'+p''$, then either $p>0$ or $p\equiv 0$.

Proof 1: Define $$f(x)=e^x\left(p(x)-2p'(x)+p''(x)\right).$$ Then $\lim\limits_{x\to-\infty}f(x)=0$ and $$f'(x)=e^x\left(p(x)-p'(x)-p''(x)+p'''(x)\right)\ge 0,$$ i.e. $f$ is increasing. It follows that $f\ge 0$, and hence $$p-2p'+p''\ge 0.$$ Define $$g(x)=e^{-x}\left(p(x)-p'(x)\right).$$ Then $\lim\limits_{x\to+\infty}g(x)=0$ and $$g'(x)=-e^{-x}\left(p(x)-2p'(x)+p''(x)\right)\le 0,$$ i.e. $g$ is decreasing. It follows that $g\ge 0$, and hence $$p-p'\ge 0.$$ Define $$h(x)=e^{-x}p(x).$$ Then $\lim\limits_{x\to+\infty}h(x)=0$ and $$h'(x)=-g(x)\le 0,$$ i.e. $h$ is decreasing. Therefore, either $h>0$ or $h\equiv 0$. The conclusion follows.

Proof 2: Denote $q=p-p'$. Then $$p+p'''\ge p'+p''\iff q-q''\ge 0.$$ It implies that $\deg(q-q'')=\deg q=\deg p$ must be even. Therefore, $q$ has a global minimum value point, say $x_q$. Then $$q(x)\ge q(x_q)\ge q''(x_q)\ge 0,$$ i.e. $$p\ge p'.$$ Similarly, $p$ also has a global minimum value point, say $x_p$. Then $$p(x_p)\ge p'(x_p)= 0.$$

If $p(x_p)>0$, we are done. To complete the proof, suppose that $p(x_p)=0$ and let us show that $p\equiv 0$ by reduction to absurdity. If $p(x_p)=0$ and $p$ is not constant, then there exists an integer $k\ge 1$, such that $p(x)=(x-x_p)^k r(x)$ for some polynomial $r$ with $r(x_p)\ne 0$. Since $x_p$ is a minimum point of $p$, $k$ must be even. Then $$p(x)-p'(x)=-kr(x_p)(x-x_p)^{k-1}+O((x-x_p)^k)$$ cannot be always non-negative, a contradiction.

  • $\begingroup$ @GitGud: Since $f$ is increasing and $f(-\infty)=0$, $f\ge 0$. $\endgroup$ – 23rd Jul 31 '13 at 19:42
  • $\begingroup$ Of course, thanks. $\endgroup$ – Git Gud Jul 31 '13 at 19:44
  • $\begingroup$ @GitGud: You are welcome. $\endgroup$ – 23rd Jul 31 '13 at 19:47
  • $\begingroup$ @23rd: From $h$ decreasing and $\lim _{x \to \infty} h(x)=0$ ,how do you conclude either $h \equiv 0$ or $h>0$ ? I seem to only conclude $h \ge 0$ .... $\endgroup$ – Souvik Dey Jan 3 '15 at 12:41
  • $\begingroup$ @SouvikDey: Please note that: (1) $h(x)=0$ if and only if $p(x)=0$; (2) $p$ is a polynomial. $\endgroup$ – 23rd Jan 6 '15 at 16:34

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.